Harmony and Existential Fulfillment: A Comparative Study of Wu-Wei Philosophy and Jean-Paul Sartre’s Perspectives - Elikwu, Juliet Nwenenne (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2024)
Jean-Paul Sartre’s existential philosophy has been the subject of extensive scholarly debate, which revolves around reflections on human existence, freedom, and responsibility. Yet, so little literature is recorded in academic discourse regarding a comparative analysis between Sartre’s existential perspectives and the ancient Chinese Wu-Wei philosophy concerning life’s fulfillment. This study address this void by examining the cultural contexts of France and China. The primary objective is to investigate the similarities and differences between Wu-Wei philosophy, Jean-Paul Sartre’s existential fulfillment, and the concept of harmony from both a Western existentialist viewpoint and an Eastern philosophical tradition. Drawing on theoretical knowledge from cultural philosophy, existentialism, and comparative philosophy, this study aims to clarify how individuals in Chinese and French cultures navigate their existence and seek fulfillment. Preliminary findings unravel a captivating divergences and convergences between Wu-Wei and Sartre’s perspectives. While Wu-Wei emphasizes alignment with the natural flow and spontaneity, Sartre’s existentialism focuses on authentic choice and freedom. The study exposes a fresh worldview on universal philosophical themes that promotes intercultural dialogue, and sheds light on approaches to life’s complexities. Ultimately, this study significantly adds to existing knowledge by highlighting the pivotal role of a comparative study between Wu-Wei philosophy and Sartrean perspectives.